The Effects of Curcumae Longae Radix, Curcuma phaeocaulis Radix and Their Processed Products on Epo/EpoR Pathway and CD62p - Chen, Zhimin; Li, Wenbing; Quan, Liang; Zhou, Haiting; Zhao, Yongfeng; Zhang, Xi; Hu, Lin; Hu, Changjiang (Frontiers in Pharmacology, 2018)
Background: Curcuma Radix (Yujin) is widely used to treat Qi stagnation due to Liver depression (LDQS) in traditional Chinese medicine (TCM) for a long time and good at dispelling melancholy by soothing liver to regulating Qi and relieving pain by promoting blood circulation for removing blood stasis. Yujin stir-frying with vinegar can strengthening the effect of dispersing stagnated hepatoqi to stop pain by injection of medicine into the liver and stir-frying with wine can strengthening the effect of promoting blood circulation for removing blood stasis. Due to the reason for the enhancement of clinical efficacy by processing is not clear, it is difficult to select and use processed products in the clinic. Aim/hypothesis: In this study, we start from the platelet function point of view to investigate the mechanism of promoting blood circulation and removing blood stasis and enhancing clinical efficacy by processing. Methods: This study mainly took Curcuma Longa Radix and Curcuma phaeocaulis Radix as the research subject. They are genuine regional drugs in Sichuan, China. A rat model of blood stasis induced by LDQS was established by giving the tail clamp stimulation and subcutaneously injected epinephrine hydrochloride and treated with an effective dose (0.9g·kg-1) according to the conversion of human clinical dosage for two weeks. After the experiment, the serum levels of Erythropoietin were determined by ELISA. Furthermore, to characterize the regulation of EpoR in the hepatic tissue, RT-PCR and WB were employed to detect mRNA and protein expression levels. The application flow cytometry detection of peripheral blood CD62p. Results: In the rat models, the levels of Epo、EpoR and CD62p were significantly increased. After intragastric administration of Yujin, each index has a different degree of callback. HSYJ is better than LSYJ, and the processed product by stir-frying with wine is better than other processed products. Conclusions: These results show that the mechanism of promoting blood circulation for removing blood stasis in Yujin may be to inhibit the activation and aggregation of platelets by intervening the Epo/EpoR pathway and down regulating CD62p. Stir-frying with wine can enhance this effect.